(untitled) (Jurnal Manajemen dan Organisasi, 2026)
This study aims to analyze the influence of herding bias, overconfidence bias, and availability bias on investment decisions, both directly and through the mediation of financial literacy in MSMEs in Jepara. The research sample of 233 respondents was determined by non-probability with a purposive sampling method. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) using SmartPLS 4. The results showed that directly herding bias (β = 0.143; p = 0.026) and overconfidence bias (β = 0.158; p = 0.048) had a significant positive effect on investment decisions, while availability bias (β = 0.048; p = 0.520) had no significant effect. Indirectly, financial literacy can mediate the influence of herding bias (β = 0.065; p = 0.032), overconfidence bias (β = 0.239; p = 0.000), and availability bias (β = 0.084; p = 0.013) on investment decisions. The model has an R² of 0.507 for investment decisions and 0.568 for financial literacy. Empirical findings confirm that financial literacy plays a significant role in improving the quality of investment decisions of MSMEs, so its improvement is necessary to reduce the influence of behavioral bias and encourage more rational and optimal investment decisions.